Synergistic effect of PCPE1 and sFRP2 on the processing of procollagens via BMP1. Issue 7 (21st March 2019) - Zhu, Qin; Guo, Wei; Zhang, Shengjie; Feng, Yang; Wang, Xiao; Greenspan, Daniel S.; Zhou, Libin; Huang, Guo‐Ru
Abstract : This article corrects: Synergistic effect of PCPE1 and sFRP2 on the processing of procollagens via BMP1, Volume 593, Issue 1, 119–127. Article first published 09 November 2018. https://doi.org/10.1002/1873-3468.13291 Dr Daniel S. Greenspan was inadvertently omitted from the list of authors in the original publication. The correct list of authors is as shown above. Dr Daniel S. Greenspan affiliation and contact details are as follows: Department of Cell and Regenerative Biology, University of Wisconsin, Room 4503, WIMRII, 1111 Highland Ave, Madison, WI 53705, dsgreens@wisc.edu